Petrology and Mineralogy of Metamorphic Rocks in The Pringsewu District, Lampung Province, Indonesia - Happy Christin Natalia Sirait; Veni Dewinta (Journal of Geoscience, Engineering, Environment, and Technology, 2023)
The origin of metamorphic rock is greatly influenced by the temperature and pressure changes in every tectonic setting, especially in active subduction margins. One of the wide outcrops of metamorphic rock occurs in the Pringsewu District, Lampung, and it is a part of the Palaeozoic Gunung Kasih Complex. The presence of metamorphic rocks in Pringsewu has raised several questions and debates for some time due to the lack of research and field evidence found in this area, especially, since the origin of metamorphic rock in Lampung has been rarely studied. This research aims to determine the metamorphic rock facies and the tectonic setting underlying the formation of metamorphic rocks in the study area. Petrographic analysis on 19 thin-section samples shows that metamorphic rock in the research area can be divided into two regions i.e., western and eastern regions. The Eastern part is characterized by muscovite-epidote schist and greenschist which consist of quartz, muscovite, actinolite, epidote, and garnet as index minerals. Whereas the western part is characterized by quartzite and biotite-epidote schist that consist of quartz, biotite, and muscovite. Based on the mineral index, metamorphic rock’s protoliths are pelitic rock, mafic rock, and quartz-feldspathic sandstone. The metamorphic rock zonation shows the created temperature is from 280-550oC. The foliation structure such as schistose and porphyroblastic texture in the whole rocks sample indicated that metamorphic rocks are created in medium-grade metamorphism and are characterized by the greenschist facies to epidote-amphibolite facies. The abundance of quartz, k-feldspar, and labradorite minerals show that metamorphic rocks came from the microcontinent which was caused by a collision between the intra-oceanic Woyla plate and West Sumatra microcontinent in the Cretaceous. Indications of tectonic activity that create the lithology in Lampung Province need more geological study, especially to determine the absolute age of the metamorphic rock.